Perancangan Sistem Informasi Kepegawaian Berbasis Web Pada Badan Nasional Penanggulangan Bencana - Wahyudi, Eko; Mukhayaroh, Anna (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System; Vol 10 No 1 (2025): INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS (Juni 2025), 2025)
The National Disaster Management Agency (BNPB) faces various challenges in managing employee data manually using Microsoft Excel, such as data entry errors, delays in data updates, and inefficiencies in leave requests and attendance monitoring. This study aims to design and develop a web-based Human Resource Information System to improve efficiency, accuracy, and transparency in employee data management at BNPB. The system was designed using the prototyping method, enabling iterative development based on user feedback. The research results show that this system can integrate processes for employee data management, leave requests, and attendance management. The system also provides real-time data access to facilitate managerial decision-making. With the features provided, the implementation of this information system is expected to enhance operational efficiency and address the challenges previously faced by BNPB.